2014
DOI: 10.1371/journal.pone.0085011
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is Enough? Minimal Responses of Water Quality and Stream Biota to Partial Retrofit Stormwater Management in a Suburban Neighborhood

Abstract: Decentralized stormwater management approaches (e.g., biofiltration swales, pervious pavement, green roofs, rain gardens) that capture, detain, infiltrate, and filter runoff are now commonly used to minimize the impacts of stormwater runoff from impervious surfaces on aquatic ecosystems. However, there is little research on the effectiveness of retrofit, parcel-scale stormwater management practices for improving downstream aquatic ecosystem health. A reverse auction was used to encourage homeowners to mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 59 publications
0
60
0
3
Order By: Relevance
“…In Figures , the brown line represents the expected trajectory of each metric if there are no SCMs installed and all run‐off is delivered to the stream untreated. On the basis of the studies described above (e.g., Bell et al, , ; Palla & Gnecco, ; Roy et al, ), treating a small portion of the impervious area often fails to produce detectible water quantity or quality changes for particular metrics. Purple lines in Figures represent the installation of SCMs in the watershed, with the length of the line representing the degree of SCM installation necessary to trigger a shift in the water quantity or quality response.…”
Section: Hysteresis Resulting From Urbanization and Stormwater Managementioning
confidence: 99%
“…In Figures , the brown line represents the expected trajectory of each metric if there are no SCMs installed and all run‐off is delivered to the stream untreated. On the basis of the studies described above (e.g., Bell et al, , ; Palla & Gnecco, ; Roy et al, ), treating a small portion of the impervious area often fails to produce detectible water quantity or quality changes for particular metrics. Purple lines in Figures represent the installation of SCMs in the watershed, with the length of the line representing the degree of SCM installation necessary to trigger a shift in the water quantity or quality response.…”
Section: Hysteresis Resulting From Urbanization and Stormwater Managementioning
confidence: 99%
“…Furthermore, there are several other characteristics of riparian restoration that make it a beneficial restoration option. Roy et al (2014) found that 30% residential participation in a rain harvesting program in a suburban neighborhood in Cincinnati, Ohio, USA was not enough to improve local stream health and suggested that additional treatment of public roads, apartment buildings, and parking lots may be required, which would require additional participation by government and private industry. For example, current approaches to catchment-scale stormwater management, such as rain gardens, infiltration systems, permeable pavements, green roofs, and stormwater harvesting systems require public support and participation, which can be difficult to obtain (Roy et al 2008, Brown et al 2016.…”
Section: Management Implicationsmentioning
confidence: 99%
“…The project offers an opportunity to evaluate methods for engaging the community in environmental protection and restoration actions, and to provide insight into public participation in decentralized stormwater initiatives for policy-makers and practitioners, gained through a combination of enquiry methods. By assessing influences on both participants and non-participants, we build on the biophysical and economic insights derived from the Shepherd Creek project in Cincinnati, Ohio, which also sought to restore a stream by installing stormwater control measures on private land (Mayer et al 2012;Roy et al 2014).…”
mentioning
confidence: 99%